Effect of phenytoin treatment on cell proliferation in the hippocampus and the heart and related neuroendocrine changes under non-stress and stress conditions. (February 2014) - Babic, S.; Jezova, D.
Abstract : Objective: Phenytoin is an antiepileptic drug that has been shown to reduce some neurotoxic effects of glutamate in states when glutamate neurotransmission is increased, such as neurodegeneration and stress. In the present study, we tested the hypothesis that treatment with phenytoin prevents stress-induced alterations in the production of new cells in the hippocampus and in the heart. Methods: Adult male Wistar rats were exposed to repeated hypokinesis (restraint, 2 hours daily) and were treated with phenytoin (20 mg/kg/day, s.c.) or vehicle for 8 days. On the 7th day, all animals were treated with 5-bromo-2'-deoxyuridine (BrdU), a marker of cell proliferation. Results: The treatment with phenytoin under both control and stress conditions resulted in an inhibitory effect on cell proliferation, which was more evident in the heart than in the hippocampus. Repeated treatment with phenytoin led to adrenal gland hypertrophy as well as to a marginal increase in plasma renin activity. Basal and stress-induced concentrations of adrenal steroids were unchanged by phenytoin administration. Discussion: Treatment with the glutamate release inhibiting drug phenytoin did not prevent negative consequences of repeated stress exposure on cell proliferation in Wistar rats. Treatment with phenytoin even deepened stress-induced reduction of cell proliferation in the heart. It cannot be excluded that the phenytoin-induced increase in plasma renin activity observed in the present study may occur during therapeutic use of phenytoin and contribute to its adverse effects.